A mixed-methods study of coping and depression in adolescent girls with polycystic ovary syndrome. Issue 3 (March 2019) - Hopkins, Casey S.; Kimble, Laura P.; Hodges, Helen F.; Koci, Anne F.; Mills, Benjie B.
ABSTRACT: Background and purpose: Polycystic ovary syndrome (PCOS) is a complex metabolic disorder associated with clinical manifestations that could be psychologically distressing to adolescent girls considering the concern of body image during the developmental stage of adolescence. Poor psychological functioning is related to increased mortality, higher health care costs, and negative health outcomes. Coping has been identified as impacting health and adaptation to illness; therefore, the purpose was to examine coping and depression in adolescent girls with PCOS. Methods: Adolescent girls, aged 13–18 years and diagnosed with PCOS completed questionnaires regarding coping and depression and participated in interviews. A convergent, parallel, mixed-method design was used. Conclusions: Girls perceived very little control over the aspects of PCOS, with menstrual irregularities and the threat of infertility reported as the most stressful and least controllable aspects of PCOS. Lower control was a predictor of greater depression among the participants. Implications for practice: Providers should strive to establish rapport with adolescent girls and ask specifically about their concerns surrounding PCOS to provide meaningful health education. Providers should also be aware of the risk for depression among this population and should routinely screen patients and keep channels of communication open regarding the symptoms of depression.